Nonlocal effects in negative triangularity TCV plasmas. (4th March 2021) - Merlo, G; Huang, Z; Marini, C; Brunner, S; Coda, S; Hatch, D; Jarema, D; Jenko, F; Sauter, O; Villard, L
Abstract: Global gradient driven gyrokinetic simulations performed with the Gyrokinetic Electromagnetic Numerical Experiment (GENE) code are used to investigate Tokamak à configuration variable (TCV) plasmas with negative triangularity. Considering limited L-mode plasmas, the numerical results are able to reproduce the actual transport level over a major fraction of the plasma minor radius for a plasma with δ LCFS = − 0.3 and its equivalent with standard positive triangularity δ . For the same heat flux, a larger electron temperature gradient is sustained by δ < 0, in turn resulting in an improved electron energy confinement. In agreement with the experiments, a reduction of the electron density fluctuations is also seen. Local flux-tube simulations are used to gauge the magnitude of nonlocal effects. Surprisingly, very little differences are found between local and global approaches for δ > 0, while local results yield a strong overestimation of the heat fluxes when δ < 0 . Despite the high sensitivity of the turbulence level with respect to the input parameters, global effects appear to play a crucial role in the negative triangularity plasma and must be retained to reconcile simulations and experiments. Finally, a general stabilizing effect of negative triangularity, reducing fluxes and fluctuations by a factor dependent on the actual profiles, is recovered.